INTERACTION OF Ni^2+ IONS WITH HOMOPOLYNUCLEOTIDES CONTAINING ADENINE AND URACIL AND THEIR MONOMERS - Sorokin, V. A.; Valeev, V. A.; Degtiar, M. V.; Gladchenko, G. O.; Blagoi, Yu. P. (Biophysical Bulletin, 1970)
Interactions of Ni2+ ions with AMP, UMP, single-chain poly A, poly U, double-chain poly A poly U and three-chain poly A*2 poly U have been studied by the method of differential UV spectroscopy. The coiL->helix transition observed in polynucleotides is due to the Ni2+ ion binding to oxygen atoms of phosphate groups. The nickel coordination to bases takes place only in the case of single AMPs and single-chain poly A. The formation of a chelate N7-Ni2+-(P04) induces melting of this polymer. Melted parts form compact particles with the effective radius ~100A.KEY WORDS: UV spectroscopy, homopolynucleotides, metal ions.